Strength Exercise Confers Protection in Central Nervous System Autoimmunity by Altering the Gut Microbiota - Chen, Hao; Shen, Liping; Liu, Yingying; Ma, Xiaomeng; Long, Ling; Ma, Xueying; Ma, Lili; Chen, Zhaoyu; Lin, Xiuli; Si, Lei; Chen, Xiaohong (Frontiers in Immunology, 2021)
Exercise therapy including endurance training and resistance training is a promising nonpharmacological therapy in multiple sclerosis (MS) patients. Recent studies clearly revealed that exercise exerts beneficial impacts on gut microbiota. However, the role of gut microbiota in the immune benefits on strength exercise (one of resistance training) in central nervous system (CNS) autoimmunity is barely known. Here we show that 60-minutes strength exercises (SE) ameliorated the disease severity and neuropathology in experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis. SE increased the abundance and diversity of the gut microbiota, and decreased Firmicutes/Bacteroidetes ratio (F/B ratio) and intestinal mucosal permeability, and enrichment of several short-chain fatty acid (SCFA)-producing bacteria. Furthermore, SE reduced Th17 responses and increased Treg responses in the small intestine lymphoid tissues. Compared to control group, microbiota-depleted mice receiving SE microbiome fecal transplants had lower disease severity and neuropathology scores. These results uncovered a protection role of SE in neuroimmunomodulation effects partly via changes of gut microbiome.